Bioinformatics Analysis of a 4bp Homozygous Deletion Mutation of EDAR Gene Identified as an Important Cause of Hypohidrotic Ectodermal Dysplasia in Pakistan - Abdul Hameed; Hafsah Muhammad; Mir, Asif; Muhammad Ajmal; Siddique, Nayyer (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Hypohidrotic Ectodermal Dysplasia (HED) is a rare congenital disorder characterized by reduced hair, the absence of sweat glands, dental anomalies, and craniofacial malformations. This condition can be inherited through X-linked, autosomal recessive, or autosomal dominant modes of inheritance. Mutations in four specific genes (EDAR, EDA, WNT10A, and EDARADD) are known to cause HED. In a study to identify a pathogenic mutation in a consanguineous Pakistani family with the autosomal recessive form of HED, microsatellite markers were utilized to genotype the known loci associated with the disease. The condition in this family was mapped to the EDAR gene locus located on chromosome 2q11-q13. Upon screening the EDAR gene, a novel homozygous 4bp deletion (718delAAGA) in exon 8 was identified, which segregated with the disease phenotype. This 4bp deletion in the EDAR gene results in a frameshift and early termination of translation, producing a truncated protein of 245 amino acids instead of the normal length of 539 amino acids. Various bioinformatics tools were employed to analyze the pathogenic mutation linked to a significant number of HED cases in Pakistan. I-TASSER was used to model the protein structure, CASTp facilitated the identification of various pockets, and STiTCH 3.1 determined EDA to be the ligand for EDAR. Docking analysis were conducted for both the mutant and wild-type EDAR proteins with EDA, revealing notable differences in the interaction sites between the docked complexes of the normal and mutant forms of EDAR with the ligand EDA. These analyses provided insights into the protein's structural features, active sites, interactions, and the overall impact of the mutation.